Mekanisma Pembelajaran Organisasi (OLM) serta Hubungannya dengan Komitmen Organisasi Jabatan Perkhidmatan Haiwan Negeri Kedah Darul Aman - Mohd. Noor Hisham, Mohd. Haron (2004)

(untitled)
The exploration of relationship between organizational commitment and organizational learning mechanism is still new and not much work has been done. Although there have been several studies reported on training and organizational commitment in the Western, very little has been utilize in respect of the local professionals in Malaysia. This research investigates the association between four factors in organizational learning mechanism (learning environment, identifying learning and development needs, meeting learning and development needs, and applying learning in a workplace). For that reason OLM instrument named Learning Environment Questionnaire (LEQ) were used. This instrument consist 65 items blend in twelve scales to study the four dimensions. Both organizational and occupational commitment studied by using the three dimension of commitment (affective commitment, continuance commitment, and normative commitment). A few demographic factors were also studied to see the relationship with the commitment. Result of the study shows that OLM were strongly related with the organizational commitment. Factor of work experience and age group at least in the studied organizational shows no differences with the affective, continuance and organizational commitment. Education level also doesn’t seem to have any differences towards the organizational commitment and his dimensions.